Compact Enhanced CPW-Fed Antenna for UWB Applications - Abdi, H.; Nourinia, J.; Ghobadi, C. (Advanced Electromagnetics, 2021)
This paper presents a compact antenna with co-planar waveguide (CPW) feed line for ultra-wideband (UWB) applications. The proposed antenna consists of a beveled radiating patch with wide rectangular slit at its upper side and a partial ground plane with insertion of symmetrically two-step beveled tapers at its center and sides, which provides a wide operating bandwidth. The antenna is integrated with narrow rectangular-shaped parasitic elements with different lengths placed adjacent to radiant patch to significantly enhance the impedance matching and bandwidth, especially at the upper frequencies. The measured results show an |S11| less than -10 dB bandwidth of 2.5-19.8 GHz with 155% fractional bandwidth. Simulation results are in good agreement with experimental measurements, which exhibits the validity of the proposed design approach. Moreover, the proposed CPW-fed antenna shows omnidirectional radiation patterns with stable gain within the operational range. The proposed compact antenna with low profile, light weight, large frequency bandwidth, ease of fabrication and low cost material is suitable for UWB applications.